Simulation of potential suitable areas and analysis of natural reserves for four species of Taxus in southern China - Zhou, Yuchen; Hu, Juhua; Xie, Guanhong; Shao, Yakui; Liu, Mu (Frontiers in Forests and Global Change, 2025)
IntroductionIn southern China, four species of the Taxus genus are distributed, and identifying their suitable habitats plays an important role in species conservation.MethodsThis study used the MaxEnt model to simulate and predict the potential suitable habitat distribution for these four species. The prediction model utilized 257 occurrence points from the four yew species, along with historical climate and topographic data, and incorporated the distribution of nature reserves in China. The model’s accuracy was validated using the Area Under the Receiver Operating Characteristic Curve (AUC) to compare the effect of different function models on prediction accuracy.ResultsThe results showed that the AUC values for all four yew species exceeded 0.9, indicating a high level of reliability in the model predictions. The high-suitability area for Taxus wallichiana var. chinensis is 13,943.62 km2, with nature reserves covering 7.49% of this area; Taxus wallichiana var. mairei has a high-suitability area of 11,950.97 km2, with a coverage rate of 2.44%; Taxus wallichiana has a high-suitability area of 9,784.43 km2, with a coverage rate of 10.52%; and Taxus yunnanensis has a high-suitability area of 7,226.57 km2, with a coverage rate of 6.47%. The high-suitability areas for T. wallichiana var. chinensis are concentrated in the Qinling, Wuyi, and Hengduan mountain ranges, while T. wallichiana var. mairei has a broader distribution, primarily in the Wuyi, Qinling, Hengduan, and southeastern Himalayas. The distributions of T. wallichiana and T. yunnanensis are concentrated in the Hengduan Mountains and southeastern Himalayas.DiscussionThe study suggests expanding the network of protected areas, constructing ecological corridors, and introducing cultivation efforts to enhance population stability within high-suitability zones. For T. wallichiana var. mairei and T. wallichiana var. chinensis, it is recommended to attempt more reintroduction efforts, while for T. wallichiana and T. yunnanensis, habitat protection should be prioritized. The establishment of additional natural protected areas and the construction of ecological corridors linking these protected areas are important ways to strengthen the conservation of yew species.